2021
DOI: 10.1039/d0sc05233g
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective synthesis of chiral porphyrin macrocyclic hosts and kinetic enantiorecognition of viologen guests

Abstract: Chiral guests display kinetic stereoselective threading through chiral porphyrin cages if their chirality is located at the chain ends and not in the centers, supporting the previously reported entron effect of threading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…In a previous paper we showed that the methyl groups on the chiral carbon centers of the spacers in (R,R,R,R)-H 2 C* and (S,S,S,S)-H 2 C* are located inside the cavity. [18] As can be seen in the crystal structure of (R,R,R,R)-MnC* (Figure 2b) these methyl groups are now pushed out of the cavity, because the oxygen atom of DMF coordinates to the manganese center. Furthermore, the chiral centers do not induce any chiral twist in the relative orientation of the xylylene sidewalls of the glycoluril framework.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…In a previous paper we showed that the methyl groups on the chiral carbon centers of the spacers in (R,R,R,R)-H 2 C* and (S,S,S,S)-H 2 C* are located inside the cavity. [18] As can be seen in the crystal structure of (R,R,R,R)-MnC* (Figure 2b) these methyl groups are now pushed out of the cavity, because the oxygen atom of DMF coordinates to the manganese center. Furthermore, the chiral centers do not induce any chiral twist in the relative orientation of the xylylene sidewalls of the glycoluril framework.…”
Section: Resultsmentioning
confidence: 89%
“…[18] They displayed similar but opposite Cotton effects in the circular dichroism (CD) spectra (Figure 2a), just like the chiral metal-free cages. [18] We tested two prochiral alkene substrates, the terminal conjugated alkene 7 and the alkyl bridged terminal alkene 17, under standard conditions, i. e. with excess tBuPy present. After reaction, the products were analyzed by chiral HPLC, which revealed that only racemic mixtures of products had been formed in isolated yields of 51 and 50 %, respectively.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Most recently, Elemans, Nolte and coworkers reported an unusual chiral macrocyclic porphyrin (Figure 19a, XXII) with a C2 symmetry for the kinetic enantiorecognition of chiral viologen molecules, illustrated in Figure 19b [82]. The CD spectra of the enantiomer pairs (R, R, R, R)-and (S, S, S, S)-XXII displayed mirror-image signals with bands centered at~415 nm (Figure 19c).…”
Section: Bis-porphyrin Systems and Porphyrin-tweezersmentioning
confidence: 97%